Zarządzanie zapasami w małym przedsiębiorstwie - Michalski, Grzegorz (Inventory Management in Small Enterprise, 2005)
Maximization of wealth of his owners is the basic financial aim in management of a small enterprise. Optimal inventory management contributes to the realization of this aim. The article presents methods accessible for of small enterprise for optimization of the inventory management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 190-197